Volume 4: Manufacturing Materials and Metallurgy; Ceramics; Structures and Dynamics; Controls, Diagnostics and Instrumentation; 1999
DOI: 10.1115/99-gt-451
|View full text |Cite
|
Sign up to set email alerts
|

Wake Vorticity Decay and Blade Response in an Axial Compressor With Varying Axial Gap

Abstract: This paper addresses the decay of rotor wake vorticity for a rotor/stator axial compressor, with the axial gap between blade rows being 10, 20 and 30 percent chord, and at both design and high loading levels. Experiments were conducted in a large-scale, low-speed axial compressor. Navier-Stokes calculations were also executed. Both data and Navier-Stokes results reveal that the decay of rotor wake vorticity increases substantially as the axial gap decreases; the decay for 10 percent gap is about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Van Zante et al [14] showed that viscous mixing losses are reduced due to wake stretching, which indicates a reduction in loss when axial gaps are reduced. This effect was confirmed by several studies [15][16][17]. However, shorter axial gaps will tend to increase the extent of turbulence and near wall losses due to earlier transition [18][19][20].…”
Section: Engine Performance and Aerodynamicssupporting
confidence: 60%
“…Van Zante et al [14] showed that viscous mixing losses are reduced due to wake stretching, which indicates a reduction in loss when axial gaps are reduced. This effect was confirmed by several studies [15][16][17]. However, shorter axial gaps will tend to increase the extent of turbulence and near wall losses due to earlier transition [18][19][20].…”
Section: Engine Performance and Aerodynamicssupporting
confidence: 60%
“…In the study by Wo et al [4], the researchers experimentally and numerically proved that a higher time-averaged stator load increases the rotor wake decay rate and reduces the stator's response level. Smith [5] observed that a closer axial spacing improved efficiency by more than one point and produced a higher total pressure ratio in an experiment of subsonic multistage compressors.…”
Section: Introductionmentioning
confidence: 99%